The Frayer Learning Model Assisted by Flashcard Media: Descriptive Text Writing Skills of Islamic Elementary School Students - Julita, Julita; Hidayah, Nurul; Erfayliana, Yudesta (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The purpose of this study was to describe the effect of the Frayer learning model assisted by flashcard media on descriptive writing skills in Indonesian language subjects for elementary school students. This research employs an experimental design with a nonequivalent control group. This study was conducted in Grade 2 at Islamic Elementary School Assalam Bandar Lampung. Data collection was done using observation sheets and tests. Data analysis used quantitative analysis with an independent t-test. The findings indicated that the Frayer learning model, facilitated by flashcard media, significantly and positively influenced the descriptive text writing abilities of second-grade students. The hypothesis test results, derived from an independent samples t-test, demonstrated a significance (2-tailed) value of 0.000, which is less than 0.05 (0.000 < 0.05), leading to the rejection of H₀ and the acceptance of H₁. Moreover, a substantial disparity in learning outcomes was observed between the experimental group and the control group. The experimental group employing the Frayer model achieved an average posttest score of 44.80, which was significantly superior to the control group's average posttest score of 38.70, utilizing the discovery learning method and video media. Moreover, the implementation of the Frayer learning model utilizing flashcards not only enhanced the average proficiency of students but also yielded more uniform and consistent capabilities. This data suggests that this model effectively aids most students, irrespective of their initial abilities, in attaining improved learning outcomes.